On the number of integers which form perfect powers in the way of $ x(y_1^2+y_2^2+y_3^2+y_4^2) = z^k $ - Tingting Wen (AIMS Mathematics, 2024)
Let $ k \geqslant 2 $ be an integer. We studied the number of integers which form perfect $ k $-th powers in the way of